A rare case of aerococcus urinae infective endocarditis. Issue 2 (3rd April 2017) - Tathireddy, Harsha; Settypalli, Sahitya; Farrell, John J
ABSTRACT: Introduction: Aerococcus urinae is a rare cause of infective endocarditis. Aerococcus is a gram positive cocci that is easily misidentified as Staphylococci or Streptococci. The true incidence rate of this pathogen is likely underestimated. Recent advances in laboratory diagnostic methods with matrix-associated laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS) have lead to increased recognition of this pathogen in the clinical microbiology lab, and awareness as a cause of infective endocarditis in the infectious disease community. Case reports: Aerococcus usually affects males with underlying urinary tract conditions. Herein, we report a case of prosthetic aortic valve endocarditis caused by Aerococcus urinae . Discussion: Our patient was considered high risk for cardiac surgery and was treated successfully with intravenous antibiotics alone for six weeks. Conclusion: Infective endocarditis should be considered in all cases of Aerococcus bacteremia and appropriate diagnostic evaluations pursued. Abbreviations: AV: Aortic valve; IE: Infective endocarditis